Bicyclol in the treatment of patients with chronic diffuse liver diseases - M. V. Maevskaya; V. D. Lunkov; N. I. Geyvandova; L. K. Palgova; I. Yu. Pirogova; M. K. Prashnova; N. V. Marchenko; E. N. Zinovieva; T. A. Ilchishina; V. T. Ivashkin; P. V. Koroy (Медицинский совет, 2020)
Introduction. The increase in serum transaminases (ALT and AST) and the persistence of their high values is associated with morbidity and mortality from liver diseases. Bicyclol has anti-inflammatory and antioxidant effects, which formed the basis for this study.Materials and methods. The study enrolled 51 patients (MELD < 19); hepatitis stage – 84.4%, cirrhosis – 15.6%. Treatment: Bicyclol 75 mg/day for 12 weeks. Criteria of efficacy: dynamics of ALT, AST, CRP; general well-being (D-FIS scale).Results. After 4 weeks of treatment the share of patients with ALT normalization was 50,9% (p < 0,001); with AST normalization – 62.7% (p < 0.001); after 12 weeks - 79,5% and 89,7% respectively (p < 0,001). CRP decreased statistically significantly after 2 and 4 weeks from the beginning of treatment. The D-FIS questionnaire was filled in by 36 patients at the beginning of the study, in 4 weeks - by 35 patients, in 12 weeks – by 32 patients. Median D-FIS decreased from 12 (8.2; 32.2) to 8 (5; 29) points (p < 0,001) after 4 weeks of treatment, after 12 weeks – to 6.5 (3; 28.5) points (p < 0.001). The CRP was positively correlated with the D-FIS value. Fibrosis (“Fibromax”, “Fibroscan”) was studied in 10 additional patients, the dose of Bicyclol was 150/75 mg/day during 6 months, the result was statistically significant (p < 0.001).Conclusion. Application of Bicyclol leads to reduction of fatigue, local and systemic inflammation, fibrosis in chronic diffuse liver diseases regardless of etiology.